ANALISIS PEMAHAMAN KONSEP MATEMATIS SISWA PADA PENERAPAN MODEL BLENDED LEARNING - Ghabrieliasebth Veronica; Maman Fathurrohman (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Students' ability to understand concepts is closely related to reasoning, communication, and problem solving skills. So a good understanding of concepts will help students achieve their learning goals well. This study aims to analyze and describe students' ability to understand mathematical concepts in the application of blended learning. The subjects in this study were class VIII students at SMPN 1 Sepatan, Kab. Tangerang. This type of research is descriptive qualitative. The procedures used in this study include the preparation, implementation, data analysis, and preparation stages. Data analysis techniques used in this study include Data Reductions, Data Display, and Conclusions. The results of this study there are differences in each indicator of the ability to understand students' mathematical concepts, not all indicators are met quite well. Blended learning has a good effect on the ability to understand students' mathematical concepts, this is due to face-to-face learning where students get a direct explanation of the material. This blended learning learning model is an effective and efficient learning in the implementation of distance learning.